Silicon nutrition of graminaceous crops - Jinger, Dinesh; Dhar, Shiva; Vijayakumar, S; Pande, V C; Kakade, Vijaysinha; Jat, R A; Dinesh, D (Indian Farming, 2021)
Silicon is not considered as essential component for crop growth. However, it is one of the most versatile elements in nutrient management. Application of Si not only improves productivity but also mitigates biotic and abiotic stresses. The beneficial effect of Si is more evident under stress conditions. Thus, it can be concluded that Si may a boon for improving productivity as well as the quality of the graminaceous crops particularly under.